2012
DOI: 10.1521/psyc.2012.75.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Self in Schizophrenia: A Multidimensional Examination of Short-Term Outcomes

Abstract: The manifestation, course, and prognosis of schizophrenia are extremely variable, raising an interest in the role of personality and self-concept in the illness' outcome. Building on voluminous research attesting to the fragility and instability of the self in schizophrenia, we examined the role of four self-concept aspects--self-esteem level, self-esteem instability, self-concept clarity, and the perception of the self as ill--in schizophrenia-spectrum disorders. Eighty-nine outpatients were assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Weinberg et al . () reported two‐edge phenomena. Self‐concept involves clarifying subjective experience in improving personal well‐being and quality of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Weinberg et al . () reported two‐edge phenomena. Self‐concept involves clarifying subjective experience in improving personal well‐being and quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, depression is associated with a higher perception of the self as being ill (Weinberg et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…To determine the effect of the level of perceived sports competence and perceived physical fitness (PSCPF, high versus low) [30,31] on 6MWD, Vancampfort et al [32] compared the distances walked by individuals with schizophrenia (n ¼ 38). The authors reported a longer distance for participants with higher levels of PSCPF (648.0 m ± 68.6 versus 538.0 m ± 89.5, p50.001).…”
Section: Mwd Comparisons: Patients With Schizophrenia Versus Controlmentioning
confidence: 99%
“…Previous research in people with schizophrenia has found that SCC is negatively correlated with depression and anxiety symptoms (Bigler, Neimeyer, & Brown, 2001) and internalized stigma (Hasson-Ohayon et al, 2014). However, previous work has yielded mixed results about whether SCC is associated with positive symptoms, finding that SCC is negatively correlated with positive symptoms at baseline, but positively associated with an increase in positive symptoms at a follow-up (Noyman-Veksler, Weinberg, Fennig, Davidson, & Shahar, 2013; Weinberg et al, 2012). Similarly, these studies found that SCC was negatively correlated with negative symptoms.…”
Section: Introductionmentioning
confidence: 95%